Consumer Attitude, Consumer Trust, and Price Perception on Purchace Decision - nikma yucha; Trio Ardianto; Berlian Putri K (Journal of Applied Management and Business, 2022)
The purpose of this studyis to determine if consumer attitudes, consumer confidence and awareness of prices influence purchasing decisions at KebabQue Sepanjang. The survey used questionnaires to collect data, and the consumer population of KebabQue MSME is not yet known.  The sample is taken using the Lameshow formula and the result is 96, rounded up to 100.  The method used in this study is accidental sampling.  The results of this survey show that consumer attitudes have a significant impact on purchase decisions, and consumer trust has a posittive andssignificant impact on purchasing deecisions.  Price awareness has a positive and important impact on purchasing decisions.  Consumer attitudes, consumer confidence and price awareness also have a positife and important impact on purchasing decisions.  The implications of this study are that KebabQue MSME partners will continue to provide high quality foods and meet consumer needs as much as possible so that consumers can truly trust Kebab Que MSME foods.